Pengaruh Pertumbuhan Laba, Struktur Modal, dan Likuiditas terhadap Kualitas Laba Perusahaan pada PT BFI Finance Indonesia Tbk - Puspa Dwi Banowati; Umi Nadhiroh; Ririn Wahyu Arida (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to explain and test the hypotheses regarding the effect of Profit Growth, Capital Structure, and Liquidity Ratio on Earnings Quality. A quantitative approach with an associative method was employed to examine the influence of Profit Growth, Capital Structure, and Liquidity Ratio on Earnings Quality at PT BFI Finance Indonesia Tbk during the 2016–2023 period. The data analyzed are secondary data obtained from financial statements and earnings quality records listed on the Indonesia Stock Exchange. The analysis was conducted using multiple linear regression with both partial and simultaneous hypothesis testing. The partial analysis results indicate that Profit Growth has a negative and significant effect, Capital Structure has a negative and insignificant effect, while Liquidity Ratio has a positive and insignificant effect on Earnings Quality. Simultaneously, the three variables were found to have a significant effect on Earnings Quality. The contribution of Profit Growth, Capital Structure, and Liquidity Ratio to Earnings Quality is 60.7%, while the remaining 39.3% is influenced by other variables not included in this study.